Uric Acid: A Potential Marker For Predicting Maternal And Fetal Morbidity - Aeman Javed; Umber Arooj Tahir; Hafsa Tauseef; Syeda Luba Hussain; Sana Shaukat Siddiqui (Journal of Rawalpindi Medical College, 2024)
Objective: To find out serum uric acid levels in normal and preeclamptic pregnant women in the third trimester.